Compact, flexible and highly selective wideband complementary FSS with high angular stability - Coomar, Srimita; Mondal, Santanu; Sanyal, Rajarshi (International journal of microwave and wireless technologies, 2022)
This article presents a novel miniaturized (0.105λ0 × 0.105λ0) flexible complementary frequency selective surfaces (CFSS) structure with sharp band edge selectivity and very high angular stability. To explore two diverse applications as a passband and stopband filter, a novel complementary convoluted square loop (CCSL) type structure has been designed and investigated on ultrathin dielectric material of thickness 0.0023λ0. The second-order wide controllable passband with fractional bandwidth of 19.23% (−3 dB) and remarkably wide stopband of 64.7% (−10 dB) and 54.8% (−20 dB) respectively have been achieved by using a cascaded resonating structure which is composed of asymmetrical meandered CCSL array, arranged on two ultrathin dielectric layers with air foam separation. This particular format would lead to sharp band edge selectivity with steep roll-off (72.43 dB/GHz) and an excellent passband selectivity factor (0.731). An equivalent lumped LC circuit in conjunction with the transmission line model has also been adopted to comprehend the physical mechanism of the proposed single layer and double layer structures. Further, better passband and stopband angular stability at an oblique incident angle of 45° and the bending characteristics have also been investigated thoroughly for the proposed flexible CFSS to check their employability in different conformal structures with WiMAX passband and WLAN stopband application.